2022
DOI: 10.2147/clep.s376068
|View full text |Cite
|
Sign up to set email alerts
|

Design for a Multicentre Prospective Cohort for the Assessment of Platelet Function in Patients with Hepatitis-B-Virus-Related Acute-on-Chronic Liver Failure

Abstract: Background: Acute-on-chronic liver failure (ACLF) has high short-term mortality and lacks sufficient medical therapy. Available algorithms are unable to precisely predict short-term outcomes or safely stratify patients with ACLF as emergent liver transplantation candidates. Therefore, a personalized prognostic tool is urgently needed. Purpose: Platelet function and its clinical significance in ACLF patients with chronic hepatitis B virus (HBV) infection have not been investigated. This study aimed to assess ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Moreover, a previous investigation 14 showed moderate to good correlation between the 2 VCM‐Vet devices used, and some reported technical issues make it challenging to adequately interpret the results. In our study, we elected to use an established reference interval, as well as a control group, for data interpretation, which is commonly done in people in multicenter studies involving TEG 34 , 35 , 36 , 37 , 38 or ROTEM. 35 , 36 , 39 The data also was assessed for interlaboratory instrument variability across the 2 institutions.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a previous investigation 14 showed moderate to good correlation between the 2 VCM‐Vet devices used, and some reported technical issues make it challenging to adequately interpret the results. In our study, we elected to use an established reference interval, as well as a control group, for data interpretation, which is commonly done in people in multicenter studies involving TEG 34 , 35 , 36 , 37 , 38 or ROTEM. 35 , 36 , 39 The data also was assessed for interlaboratory instrument variability across the 2 institutions.…”
Section: Discussionmentioning
confidence: 99%
“…Through univariate and multivariate analyses, we found that SII ≥201.5 and MELD ≥27 were independent prognostic factors for 90-day mortality after surgery. Similarly, Lin et al [28] found that high neutrophil-lymphocyte ratio indicates poor prognosis for ACLF after LT. Jiang et al [29] revealed that platelet function is a prognostic marker in ACLF.…”
Section: Discussionmentioning
confidence: 99%
“…Through univariate and multivariate analyses, we found that SII ≥201.5 and MELD ≥27 were independent prognostic factors for 90-day mortality after surgery. Similarly, Lin et al [28] found that high neutrophil-lymphocyte ratio indicates poor prognosis for ACLF after LT. Jiang et al [29] revealed that platelet function is a prognostic marker in ACLF. SII, systemic immune-inflammation index; BMI, body mass index; WBC, white blood cell; Hb, hemoglobin; ALT, alanine aminotransferase; AST, aspartate aminotransferase; GGT, glutamyl transpeptidase; TB, total bilirubin; Crea, creatinine; MELD, model for end-stage liver disease score; Child, Child-Pugh scores; operation time, operation time was defined a priori as the total duration in the operating room [24]; anhepatic phase, anhepatic phase was defined from the time the cava was clamped and the liver was removed to the time that liver was perfused [25]; blood loss, blood loss was calculated as the sum of blood collected in the cell saver, in other suction systems, and that estimated to be contained in cotton swabs and compresses minus the recorded volume of fluid used to flush the surgical site and the cell-saver collection system [26]; DBD, donation after brain death; DCD, donation after cardiac death.…”
Section: Discussionmentioning
confidence: 99%